Solid-state electrolyte and preparation method thereof, and solid-state battery

CN122348254BActive Publication Date: 2026-10-23SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610805799.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-23
Estimated Expiration
2046-06-05

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种固态电解质及其制备方法、固态电池,以解决现有技术中PVDF基电解质膜内产生孔洞的问题

Benefits of technology

[0016]本发明提供的固态电解质,通过引入特定孔限直径的共价有机框架材料TpBD-(SO3Li)2,并控制其在电解质中的质量百分比、电解质表面的孔隙率以及厚度,使上述参数满足(a×b)/(c×d)在0.1至2的范围内。其中,TpBD-(SO3Li)2具有规则的孔道结构,孔限直径a nm在1 nm至5 nm之间,该介孔尺寸有助于容纳聚合物链段并构建有序的离子传输通道;其骨架上的磺酸锂基团能够与锂盐阴离子产生相互作用,促进锂盐解离,释放更多自由移动的锂离子。当TpBD-(SO3Li)2的质量百分比b%控制在5%至30%之间时,能够在聚合物基体中形成连续的离子传导网络,避免因含量过低导致改性效果不足或含量过高破坏膜的柔性。该材料的引入有效调控PVDF基体的结晶行为,显著减少干燥过程中的球晶形成,使电解质表面孔隙率c%降至10%及以下,避免了因孔洞导致的固固界面接触不良和局部电流集中问题。同时,将电解质厚度d μm控制在50 μm及以下有助于降低电池内阻。通过0.1≤(a×b)/(c×d)≤2的协同调控,确保TpBD-(SO3Li)2的孔道结构与添加量能够与电解质的孔隙率和厚度相匹配,使固态电解质兼具高离子电导率、良好的界面稳定性和抑制锂枝晶生长的能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122348254B_ABST
    Figure CN122348254B_ABST
Patent Text Reader

Abstract

In order to inhibit the formation of holes in the PVDF-based solid-state electrolyte film, improve the interface contact and improve the uniformity of lithium ion migration, the application provides a solid-state electrolyte and a preparation method thereof and a solid-state battery, which comprises a polymer, a lithium salt and a covalent organic framework material, wherein the covalent organic framework material comprises TpBD-(SO3Li)2; wherein the pore size limit diameter of the TpBD-(SO3Li)2 is a nm, 1<=a<=5; the mass percentage of the TpBD-(SO3Li)2 in the solid-state electrolyte is b%, 5<=b<=30; the porosity of the surface of the solid-state electrolyte is c%, c<=10; the thickness of the solid-state electrolyte is d mu m, d<=50; and the solid-state electrolyte satisfies the following condition: formula 1: 0.1<= (a x b) / (c x d) <=2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a solid electrolyte, its preparation method, and a solid battery. Background Technology

[0002] Polymer solid-state electrolytes (SSEs) offer advantages such as low raw material and processing costs, and good flexibility. They are compatible with roll-to-roll production processes, and the polymer itself acts as a binder, improving solid-solid interface contact. Furthermore, all-solid-state batteries do not require additional pressure, making them a promising candidate for large-scale industrialization. Among various polymer matrices, polyvinylidene fluoride (PVDF) stands out as a promising SSE matrix material due to its excellent dielectric properties, electrochemical stability, and mechanical properties, as well as good compatibility with fillers. However, PVDF-based electrolyte membranes are prone to spherulite formation during drying, leading to pores within the membrane. In all-solid-state battery systems, the lack of liquid electrolyte filling causes these pores to deteriorate the solid-solid interface contact. Simultaneously, the pore areas prevent uniform lithium-ion deposition, easily inducing lithium dendrite growth, which can then puncture the electrolyte membrane and cause short-circuit failure.

[0003] Therefore, there is an urgent need for a solid-state battery that can suppress the formation of pores in PVDF-based solid electrolyte membranes, improve interfacial contact, and enhance the uniformity of lithium-ion migration. Summary of the Invention

[0004] The purpose of this invention is to provide a solid electrolyte and its preparation method, as well as a solid battery, to solve the problem of pores generated in PVDF-based electrolyte membranes in the prior art.

[0005] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a solid electrolyte comprising a polymer, a lithium salt, and a covalent organic framework material, wherein the covalent organic framework material comprises TpBD-(SO3Li)2. Wherein, the pore diameter of the TpBD-(SO3Li)2 is a nm, 1≤a≤5; The mass percentage of TpBD-(SO3Li)2 in the solid electrolyte is b%, 5≤b≤30; The porosity of the solid electrolyte surface is c%, c≤10; The thickness of the solid electrolyte is d μm, where d≤50; The solid electrolyte satisfies the following conditions: Equation 1: 0.1≤(a×b) / (c×d)≤2.

[0006] Optionally, the solid electrolyte satisfies the following conditions: Equation 2: 0.5≤(a×b) / (c×d)≤1.5.

[0007] Optionally, the solid electrolyte satisfies at least one of the following conditions: (1) 2≤a≤3; (2) 10 ≤ b ≤ 25; (3) c≤4; (4) 15≤d≤30.

[0008] Optionally, the polymer includes one or both of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer.

[0009] Optionally, the lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalateborate, and lithium hexafluorophosphate.

[0010] Optionally, the mass ratio of the polymer to the lithium salt is 3:1 to 3:2, and the amount of TpBD-(SO3Li)2 added accounts for 10 to 25% of the mass percentage of the polymer.

[0011] Secondly, the present invention provides a method for preparing a solid electrolyte, comprising the following steps: 4,4'-diaminobiphenyl-3,3'-disulfonic acid and 2,4,6-tricarboxymethylphloroglucinol were mixed in an organic solvent, sonicated, and reacted with hydrogen chloride solution. After washing and drying, TpBD-(SO3H)2 was obtained. TpBD-(SO3H)2 was then subjected to an ion exchange reaction with a lithium salt solution to obtain TpBD-(SO3Li)2. The polymer, lithium salt, and TpBD-(SO3Li)2 were dissolved in N,N-dimethylformamide solution to obtain a mixed solution; The mixed solution is dried and hot-pressed on a flat plate to obtain the solid electrolyte.

[0012] Optionally, the molar ratio of the 4,4'-diaminobiphenyl-3,3'-disulfonic acid and the 2,4,6-tricarboxymethylphloroglucinol is 3:1 to 3:3.

[0013] Optionally, the organic solvent comprises dimethyl sulfoxide and N-methylpyrrolidone, and the volume ratio of dimethyl sulfoxide to N-methylpyrrolidone is 1:1; and / or, The lithium salt solution includes a lithium acetate solution.

[0014] Optionally, the reaction conditions for adding hydrogen chloride solution include reacting in a constant temperature bath at 40°C to 100°C for 72 to 168 hours.

[0015] Thirdly, the present invention provides a solid-state battery, comprising a positive electrode, a lithium metal negative electrode, and the solid electrolyte described above or prepared by the above preparation method.

[0016] The solid electrolyte provided by this invention introduces a covalent organic framework material, TpBD-(SO3Li)2, with a specific pore diameter, and controls its mass percentage in the electrolyte, the porosity of the electrolyte surface, and its thickness, ensuring that the parameters (a×b) / (c×d) are within the range of 0.1 to 2. TpBD-(SO3Li)2 has a regular pore structure with a pore diameter (a nm) between 1 nm and 5 nm. This mesopore size helps to accommodate polymer segments and construct ordered ion transport channels. The lithium sulfonate groups on its framework can interact with lithium salt anions, promoting lithium salt dissociation and releasing more freely moving lithium ions. When the mass percentage (b%) of TpBD-(SO3Li)2 is controlled between 5% and 30%, a continuous ion conduction network can be formed in the polymer matrix, avoiding insufficient modification effect due to too low a content or damage to the membrane's flexibility due to too high a content. The introduction of this material effectively regulates the crystallization behavior of the PVDF matrix, significantly reducing spherulite formation during the drying process and lowering the electrolyte surface porosity (c%) to 10% or below. This avoids poor solid-solid interface contact and localized current concentration problems caused by pores. Simultaneously, controlling the electrolyte thickness (d) in μm to 50 μm or below helps reduce the battery's internal resistance. Through synergistic regulation of 0.1≤(a×b) / (c×d)≤2, the pore structure and addition amount of TpBD-(SO3Li)2 are ensured to match the porosity and thickness of the electrolyte, enabling the solid electrolyte to possess high ionic conductivity, good interfacial stability, and the ability to suppress lithium dendrite growth. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a SEM image of the solid electrolyte of this invention without hot pressing; Figure 2 This is a SEM image of the solid electrolyte after hot pressing according to the present invention. Detailed Implementation

[0019] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0020] An embodiment of the present invention provides a solid electrolyte comprising a polymer, a lithium salt, and a covalent organic framework material, wherein the covalent organic framework material comprises TpBD-(SO3Li)2; Wherein, the pore diameter of the TpBD-(SO3Li)2 is a nm, 1≤a≤5; The mass percentage of TpBD-(SO3Li)2 in the solid electrolyte is b%, 5≤b≤30; The porosity of the solid electrolyte surface is c%, c≤10; The thickness of the solid electrolyte is d μm, where d≤50; The solid electrolyte satisfies the following conditions: Equation 1: 0.1≤(a×b) / (c×d)≤2.

[0021] Specifically, the pore diameter of the TpBD-(SO3Li)2 includes, but is not limited to, 1 nm, 2 nm, 3 nm, 4 nm, and 5 nm. The mass percentage of TpBD-(SO3Li)2 in the solid electrolyte includes, but is not limited to, 5%, 10%, 15%, 19%, 23%, 28%, and 30%. The porosity of the solid electrolyte surface includes, but is not limited to, 1%, 2%, 3%, 4%, 6%, 7%, 8%, 9%, and 10%. The thickness of the solid electrolyte includes, but is not limited to, 10μm, 20μm, 30μm, 40μm, and 50μm; The solid electrolyte provided by this invention introduces a covalent organic framework material, TpBD-(SO3Li)2, with a specific pore diameter, and controls its mass percentage in the electrolyte, the porosity of the electrolyte surface, and its thickness, ensuring that the parameters (a×b) / (c×d) are within the range of 0.1 to 2. TpBD-(SO3Li)2 has a regular pore structure with a pore diameter (a nm) between 1 nm and 5 nm. This mesopore size helps to accommodate polymer segments and construct ordered ion transport channels. The lithium sulfonate groups on its framework can interact with lithium salt anions, promoting lithium salt dissociation and releasing more freely moving lithium ions. When the mass percentage (b%) of TpBD-(SO3Li)2 is controlled between 5% and 30%, a continuous ion conduction network can be formed in the polymer matrix, avoiding insufficient modification effect due to too low a content or damage to the membrane's flexibility due to too high a content. The introduction of this material effectively regulates the crystallization behavior of the PVDF matrix, significantly reducing spherulite formation during the drying process and lowering the electrolyte surface porosity (c%) to 10% or below. This avoids poor solid-solid interface contact and localized current concentration problems caused by pores. Simultaneously, controlling the electrolyte thickness (d) in μm to 50 μm or below helps reduce the battery's internal resistance. Through synergistic regulation of 0.1≤(a×b) / (c×d)≤2, the pore structure and addition amount of TpBD-(SO3Li)2 are ensured to match the porosity and thickness of the electrolyte, enabling the solid electrolyte to possess high ionic conductivity, good interfacial stability, and the ability to suppress lithium dendrite growth.

[0022] In some embodiments, the solid electrolyte satisfies the following conditions: Equation 2: 0.5≤(a×b) / (c×d)≤1.5.

[0023] Specifically, when the solid electrolyte further meets the limitations of Formula 2, a better matching relationship is achieved between the pore size and addition amount of TpBD-(SO3Li)2 and the porosity and thickness of the electrolyte membrane, which further improves the ion transport efficiency, makes lithium ion migration more uniform, and helps to extend the cycle life of solid batteries.

[0024] In some embodiments, the solid electrolyte satisfies at least one of the following conditions: (1) 2≤a≤3; (2) 10 ≤ b ≤ 25; (3) c≤4; (4) 15≤d≤30.

[0025] Specifically, by optimizing parameters such as pore diameter, TpBD-(SO3Li)2 mass percentage, porosity, and thickness, the performance of solid electrolytes can be specifically optimized. Selecting a narrower pore diameter range helps improve the selectivity for lithium-ion transport; adjusting the TpBD-(SO3Li)2 mass percentage can further optimize the balance between ionic conductivity and mechanical properties; controlling the porosity at a lower level can minimize interface defects; and using a thinner electrolyte membrane helps reduce battery internal resistance and improve energy density.

[0026] In some embodiments, the polymer includes one or both of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer.

[0027] Specifically, when the polymer is selected from polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene copolymer, it has excellent dielectric properties and electrochemical stability, and can form good interfacial compatibility with TpBD-(SO3Li)2. The hexafluoropropylene unit in polyvinylidene fluoride-hexafluoropropylene copolymer can further reduce the crystallinity of the polymer and work synergistically with the pore structure of TpBD-(SO3Li)2 to provide more amorphous regions for lithium ion migration.

[0028] In some embodiments, the lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalateborate, and lithium hexafluorophosphate.

[0029] Specifically, the lithium salts mentioned above have high dissociation constants and good thermal stability. Under the action of the sulfonic acid groups of TpBD-(SO3Li)2, the dissociation process of lithium salts is further promoted. At the same time, the covalent organic framework material can anchor lithium salt anions and effectively inhibit anion migration, thereby increasing the lithium ion transference number.

[0030] In some embodiments, the mass ratio of the polymer to the lithium salt is 3:1 to 3:2, and the amount of TpBD-(SO3Li)2 added accounts for 10 to 25% of the mass percentage of the polymer.

[0031] Specifically, when the mass ratio of polymer, lithium salt, and TpBD-(SO3Li)2 is controlled within this range, the components can fully exert their synergistic effect. An appropriate amount of lithium salt ensures a sufficient source of lithium ions, and the amount of TpBD-(SO3Li)2 added is adapted to its pore structure, forming a uniformly distributed ion conduction network in the polymer matrix, enabling the solid electrolyte to possess high ionic conductivity, good mechanical strength, and stable interfacial properties.

[0032] In some embodiments, the present invention also provides a method for preparing a solid electrolyte, comprising the following steps: 4,4'-diaminobiphenyl-3,3'-disulfonic acid and 2,4,6-tricarboxymethylphloroglucinol were mixed in an organic solvent, sonicated, and reacted with hydrogen chloride solution. After washing and drying, TpBD-(SO3Li)2 was obtained. TpBD-(SO3Li)2 was then subjected to an ion exchange reaction with a lithium salt solution to obtain TpBD-(SO3Li)2. The polymer, lithium salt, and TpBD-(SO3Li)2 were dissolved in N,N-dimethylformamide solution to obtain a mixed solution; The mixed solution is dried and hot-pressed on a flat plate to obtain the solid electrolyte.

[0033] Specifically, the solid electrolyte preparation method provided by this invention first involves ultrasonically mixing 4,4'-diaminobiphenyl-3,3'-disulfonic acid and 2,4,6-tricarboxymethyl phloroglucinol in an organic solvent, reacting the mixture under the action of hydrogen chloride, and then washing and drying to obtain TpBD-(SO3Li)2. This TpBD-(SO3Li)2 is then subjected to ion exchange with a lithium salt solution to obtain TpBD-(SO3Li)2 with lithium sulfonate functional groups. This synthetic route ensures the successful grafting of sulfonic acid groups onto the inner wall of the covalent organic framework pores, providing active sites for promoting lithium salt dissociation. The polymer, lithium salt, and TpBD-(SO3Li)2 are co-dissolved in N,N-dimethylformamide to form a homogeneous mixed solution. The solvent is then removed by drying, allowing TpBD-(SO3Li)2 to be uniformly dispersed in the polymer matrix. During drying, its ordered pore structure can regulate the crystallization behavior of the polymer, reducing spherulite formation. Finally, a flat plate hot-pressing treatment further eliminates residual micropores, making the internal structure of the electrolyte membrane more compact and improving the solid-solid interface contact.

[0034] In some embodiments, the molar ratio of the 4,4'-diaminobiphenyl-3,3'-disulfonic acid and the 2,4,6-tricarboxymethylphloroglucinol is 3:1 to 3:3.

[0035] In some embodiments, the molar ratio of the 4,4'-diaminobiphenyl-3,3'-disulfonic acid and the 2,4,6-tricarboxymethylphloroglucinol is 3:2.

[0036] Specifically, when the mass ratio of 4,4'-diaminobiphenyl-3,3'-disulfonic acid (DABDS) to 2,4,6-tricarboxymethylphloroglucinol (TFP) is controlled within this range, it is beneficial to synthesize a TpBD-(SO3Li)2 precursor with high crystallinity and regular pore structure, which provides a structural basis for subsequent ion exchange reactions and ensures that TpBD-(SO3Li)2 has good lithium-ion conductivity.

[0037] In some embodiments, the organic solvent comprises dimethyl sulfoxide and N-methylpyrrolidone, and the volume ratio of the dimethyl sulfoxide to N-methylpyrrolidone is 1:1; and / or, The lithium salt solution includes a lithium acetate solution.

[0038] Specifically, dimethyl sulfoxide or N-methylpyrrolidone are selected as organic solvents, which can fully dissolve the reactants and provide a suitable solvent environment for the growth of covalent organic frameworks. Lithium acetate is used for ion exchange in the lithium salt solution, allowing lithium ions to readily replace hydrogen ions on sulfonic acid groups. Simultaneously, the acetate ions are easily removed in subsequent processing, avoiding residual impurities that could affect electrolyte performance.

[0039] In some embodiments, the reaction conditions for adding hydrogen chloride solution include reacting in a constant temperature bath at 40°C to 100°C for 72 to 168 hours.

[0040] Specifically, under these conditions, the reaction can ensure that the covalent organic framework material is fully crystallized and forms a complete pore structure. The appropriate reaction temperature helps to control the nucleation and growth rate, avoid the formation of defective structures, and ensure that TpBD-(SO3Li)2 has a uniform pore diameter distribution, providing a stable transport channel for lithium ions.

[0041] In some embodiments, the present invention also provides a solid-state battery, comprising a positive electrode, a lithium metal negative electrode, and the solid electrolyte described above or prepared by the preparation method described above.

[0042] Specifically, the solid-state battery provided by this invention features a solid electrolyte that forms a good solid-solid contact with the positive and lithium negative electrodes inside the battery. The introduction of TpBD-(SO3Li)2 effectively suppresses the formation of pores in the PVDF-based electrolyte membrane, allowing lithium ions to be uniformly deposited at the electrolyte-electrode interface and avoiding lithium dendrite growth induced by local overpotential. The lithium sulfonate group promotes lithium salt dissociation, and the covalent organic framework anchors anions, enabling the battery to maintain a high lithium-ion transference number and stable interfacial impedance during charge and discharge. Therefore, this solid-state battery can achieve stable capacity performance and a longer cycle life during cycling.

[0043] The present invention will be further illustrated by the following examples.

[0044] Example 1 The preparation method of TpBD-(SO3Li)2 is as follows: 4,4'-Diaminobiphenyl-3,3'-disulfonic acid and 2,4,6-tricarboxymethyl phloroglucinol were added to a mixed solvent of dimethyl sulfoxide and N-methylpyrrolidone at a molar ratio of 3:2. The mixture was ultrasonically dispersed, and hydrochloric acid solution was added. The reaction was carried out at 60°C for 144 hours. The reaction product was washed sequentially with N-methylpyrrolidone, dimethyl sulfoxide, acetone, and water, and then vacuum dried to obtain TpBD-(SO3Li)2. TpBD-(SO3Li)2 was then added to a lithium acetate solution for ion exchange at 60°C. After washing and drying, TpBD-(SO3Li)2 was obtained. The pore size of TpBD-(SO3Li)2 was measured to be 2.5 nm.

[0045] The preparation methods of solid electrolytes and solid batteries are as follows: In a glove box, polyvinylidene fluoride (polymer), lithium bis(trifluoromethanesulfonyl)imide (lithium salt), and TpBD-(SO3Li)2 were added to N,N-dimethylformamide, wherein the mass ratio of polyvinylidene fluoride (polymer) to lithium bis(trifluoromethanesulfonyl)imide (lithium salt) was 3:2, and the mass percentage of TpBD-(SO3Li)2 was 20%. The mixture was stirred and dispersed evenly. The resulting mixed solution was poured onto a scraper and coated with a 200 μm thick film using a scraper. The scraper was then transferred to a vacuum oven and dried at 80 °C for 18 hours to obtain an unpressed electrolyte membrane (e.g., ...). Figure 1 (As shown). The electrolyte membrane is subjected to flat plate hot pressing to obtain a hot-pressed solid electrolyte (e.g.). Figure 2 As shown in the figure, its porosity is 4% and its thickness is 20 μm. The positive electrode, solid electrolyte and lithium foil are stacked in sequence to assemble a soft-pack all-solid-state battery.

[0046] The test method for the pore diameter of TpBD-(SO3Li)2 is nitrogen adsorption method; The method for testing the porosity of the solid electrolyte surface is as follows: take scanning electron microscope images of the electrolyte surface before and after hot pressing, and use ImageJ software to calculate the porosity of the electrolyte surface.

[0047] Example 2-22 Examples 2-22 are mostly the same as those in Example 1, with the differences shown in Table 1.

[0048] Comparative Examples 1-8 Comparative Examples 1-8 are largely the same as those in Example 1, with the differences shown in Table 1.

[0049] Table 1. Parameter Table for Examples and Comparative Examples Comparative Example 9 Comparative Example 9 is similar to Example 1 in most steps, except that the solid electrolyte does not contain the covalent organic framework material TpBD-(SO3Li)2.

[0050] Performance testing: (1) Ionic conductivity test: Use a micrometer to test the thickness of the electrolyte and test the impedance of the symmetrical battery (stainless steel sheet / / solid electrolyte / / stainless steel sheet). Calculate the ionic conductivity according to the following formula: σ=L / (R∙S), σ: ionic conductivity, L: electrolyte thickness, R: stainless steel to battery resistance, S: stainless steel electrode area.

[0051] (2) Lithium-ion transference number: A lithium-ion symmetric cell (Li / / solid electrolyte / / Li) was used, and the lithium-ion transference number was tested using the Bruce-Vincent-Evans method. First, the AC impedance spectrum of the symmetric cell before polarization was measured using an electrochemical workstation, with a frequency range of 1 MHz to 0.1 Hz and a perturbation voltage of 5 mV. Then, a DC polarization voltage of 10 mV was applied to the cell, and the current change curve over time was recorded to obtain the initial current I0 and the steady-state current I. ss After polarization, the AC impedance was tested again to obtain the interface impedances R0 and R before and after polarization. ss The lithium-ion transport number is calculated using the formula: (3) Cyclic performance test: 100 charge-discharge cycles were performed at 25℃ and 0.2C / 0.2C current density.

[0052] Capacity retention rate = (Discharge capacity at cycle 100 / Discharge capacity at cycle 1) * 100% The performance test results of the examples and comparative examples are shown in Table 2.

[0053] Table 2 Performance test results of the examples and comparative examples According to the performance test results above, in Comparative Example 1, the (a×b) / (c×d) value is 0.08 (less than 0.1), which is outside the range. The channel conduction effect provided by TpBD-(SO3Li)2 is insufficient. The small pore diameter restricts the intercalation of polymer segments and ion transport. At the same time, the thicker solid electrolyte increases the internal resistance. The small amount of TpBD-(SO3Li)2 added makes it difficult to form a continuous conduction network, resulting in poor ionic conductivity, low lithium-ion transference number, and low cycle capacity retention. The performance test results of Comparative Example 2 show that the (a×b) / (c×d) value is much greater than 2, which is outside the range and leads to deterioration of interface stability. Although the thinner solid electrolyte and low porosity are beneficial to reducing internal resistance, the excessive TpBD-(SO3Li)2 content, combined with the extremely low porosity and thickness, destroys the flexibility of the polymer, leading to increased brittleness of the solid electrolyte membrane, poor solid-solid interface contact, and the extremely thin solid electrolyte is prone to short circuit risk, resulting in extremely short cycle life.

[0054] Comparative Example 3 has a pore diameter of less than 1 nm, which is below the 1-5 nm range. The microporous structure cannot effectively accommodate polymer segments to build an ordered ion transport channel, resulting in obstructed lithium-ion transport and a significant decrease in ionic conductivity. Comparative Example 4 has a pore diameter that is too large (greater than 5 nm). Although the calculated value of (a×b) / (c×d) is within the range, the large pore size weakens the anchoring effect of the mesoporous confinement on anions and reduces the specific surface area advantage of the material, resulting in a decrease in lithium salt dissociation efficiency, low lithium-ion transference number, and a decrease in mechanical strength due to the macroporous structure. The solid electrolyte is prone to deformation during cycling, resulting in reduced cycling performance.

[0055] In Comparative Example 5, b=3 (less than 5), the amount of TpBD-(SO3Li)2 added was too low. Although (a×b) / (c×d) was 0.15, which was within the range, a continuous ion conduction network was not actually formed in the polymer matrix, resulting in insufficient modification effect, low ionic conductivity, and short cycle life. In Comparative Example 6, b=50 (greater than 30), the amount of TpBD-(SO3Li)2 added was too high, which destroyed the mechanical flexibility of the solid electrolyte, making the solid electrolyte brittle and prone to cracking. In addition, the uniformity of the solid electrolyte film formation was poor, and lithium salts accumulated locally, resulting in extremely high interfacial impedance, making it difficult for the battery to cycle normally and extremely short cycle life.

[0056] Comparative Example 7, c=20 (greater than 10), surface porosity exceeds the limit range, TpBD-(SO3Li)2 failed to effectively control the crystallization behavior of PVDF, forming a large number of spherulites and pores. High porosity leads to poor solid-solid interface contact between electrolyte and electrode, local current density concentration, and aggravation of lithium dendrite growth. Lithium dendrites pierce the electrolyte membrane, causing cell short circuit and extremely short cycle life.

[0057] The solid electrolyte of Comparative Example 8 has a thickness greater than 50 µm. The excessively thick electrolyte significantly increases the battery's internal resistance, extends the lithium-ion transport path, results in a low lithium-ion transference number, poor rate performance, and a short cycle life.

[0058] The solid electrolyte of Comparative Example 9 does not contain TpBD-(SO3Li)2, lacks a core ion transport channel construction mechanism, the polymer crystallization behavior is not regulated, the porosity is high, resulting in low ionic conductivity, low lithium ion transference number, poor interface stability, and a cycle life far worse than that of Example 1.

[0059] In Example 1, the pore diameter, amount added, porosity, and thickness are all within the preferred range, and the polymer / lithium salt ratio and TpBD-(SO3Li)2 ratio are also preferred values. It has high ionic conductivity, high lithium ion transference number, long cycle life, and excellent overall performance.

[0060] The test results of Examples 2-5 show that when the pore diameter is at the lower limit of the range (1 nm), the pore size is too small, which limits the passage efficiency of lithium ions and polymer segments. Although the performance is better than the comparative example, the ionic conductivity is lower than that of Example 1, the lithium ion transference number is moderate, and the cycle life is slightly shorter than that of the example with a more preferred pore size. When the pore diameter is in the preferred range (2 nm), the performance is good, the ionic conductivity is high, the lithium ion transference number is high, and the cycle life is long. When the pore diameter is in the preferred range (3 nm), the performance is comparable to that of Example 3, with both ionic conductivity and lithium ion transference number being high, verifying the preference of this pore size range. When the pore diameter is in the upper limit of the range (5 nm), the pore size is too large, the anchoring effect on anions is weakened, the ionic conductivity and lithium ion transference number are relatively low, and the cycle life decreases.

[0061] The test results of Examples 6-9 show that when the amount of TpBD-(SO3Li)2 added is at the lower limit of the range (5%), the addition amount just meets the basic requirements, the continuity of the ion conduction network is insufficient, the ion conductivity and lithium ion transference number decrease, and the cycle life is better than the comparative example but lower than the example with a higher addition amount; when the amount of TpBD-(SO3Li)2 added is at the lower limit of the preferred range (10%), a continuous and effective ion conduction network is formed, the ion conductivity is high, the lithium ion transference number is high, and the cycle life is long; when the amount of TpBD-(SO3Li)2 added is at the upper limit of the preferred range (25%), the performance is good, the ion conductivity is high, the lithium ion transference number is high, and the cycle life is long; when the amount of TpBD-(SO3Li)2 added is at the upper limit of the range (30%), the ion conductivity is high, but the brittleness of the solid electrolyte membrane increases, the interface stability is slightly worse, and the cycle life is good but slightly shorter than the example within the preferred range.

[0062] The test results of Examples 10-11 show that when the porosity is within the preferred range (2%), extremely low porosity results in optimal interfacial contact. This leads to high ionic conductivity, high lithium-ion transference number, and long cycle life. When the porosity is at the upper limit of the range (10%), the performance meets the requirements, but the interfacial impedance is higher than in the low-porosity examples, ionic conductivity decreases, and cycle life is reduced.

[0063] The test results of Examples 12-14 show that when the thickness of the solid electrolyte is 10 µm, the extremely thin solid electrolyte membrane has low internal resistance and high ionic conductivity, but insufficient mechanical strength, leading to short circuits and short cycle life. When the thickness is at the upper limit of the preferred range (30 µm), safety is improved and the internal resistance remains at a low level, with high ionic conductivity and long cycle life. When the thickness is at the upper limit of the range (50 µm), the internal resistance is large, the ionic conductivity decreases, the rate performance decreases, and the cycle life is slightly reduced.

[0064] The test results of Examples 15-18 show that when the value of (a×b) / (c×d) Equation 1 is 0.13, which is close to the lower limit of the formula (0.1), the parameters are in the boundary combination. Although the performance is better than the comparative example, the ionic conductivity and lithium ion transport number decrease, and the cycle life is at a low level in the examples, which verifies the effectiveness of the lower limit of the formula. When the calculated value of Equation 1 is 0.48, which is close to the preferred range value (0.5), the ionic conductivity is high, the lithium ion transport number is high, and the cycle life is long. When the calculated value of Equation 1 is 1.33, which is in the preferred range, the ionic conductivity is high, the lithium ion transport number is high, and the cycle life is long, which is one of the combinations with excellent performance. When the calculated value of Equation 1 is the upper limit of the range (2), the pore diameter of TpBD-(SO3Li)2 is large, the anchoring effect on anions is weakened, and the ionic conductivity, lithium ion transport number and cycle life decrease compared with Examples 16 and 17, which verifies the effectiveness of the upper limit of the formula.

[0065] The test results of Examples 19-22 show that when the polymer to lithium salt mass ratio (10:3, with relatively insufficient lithium salt) exceeds the limit range, the number of freely moving lithium ions is low, the ionic conductivity and lithium ion transference number decrease, and the cycle life is low. When the mass ratio (3:1) is at the limit range, the performance is good, the ionic conductivity and lithium ion transference number are relatively high, and the cycle life increases. When the mass ratio (3:2) is at the limit range, the degree of lithium salt dissociation and TpBD-(SO3Li)2 have the best synergistic effect, resulting in high ionic conductivity, high lithium ion transference number, and long cycle life. When the mass ratio (7:5) is below the limit range, the ionic conductivity and lithium ion transference number decrease, and the cycle life is low, verifying the effectiveness of the polymer to lithium salt mass ratio in the range of 3:1 to 3:2.

[0066] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included within the protection scope of the present invention.

Claims

1. A solid electrolyte, characterized in that, Includes polymers, lithium salts, and covalent organic framework materials, wherein the covalent organic framework material includes TpBD-(SO3Li)2; Wherein, the pore diameter of the TpBD-(SO3Li)2 is a nm, 1≤a≤5; The mass percentage of TpBD-(SO3Li)2 in the solid electrolyte is b%, 5≤b≤30; The porosity of the solid electrolyte surface is c%, c≤10; The thickness of the solid electrolyte is d μm, where d≤50; The solid electrolyte satisfies the following conditions: Equation 1: 0.1≤(a×b) / (c×d)≤2; The mass ratio of the polymer to the lithium salt is 3:1 to 3:2, and the amount of TpBD-(SO3Li)2 added accounts for 10% to 25% of the mass of the polymer. The polymer includes one or both of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer.

2. The solid electrolyte according to claim 1, characterized in that, The solid electrolyte satisfies the following conditions: Equation 2: 0.5≤(a×b) / (c×d)≤1.

5.

3. The solid electrolyte according to claim 1, characterized in that, The solid electrolyte satisfies at least one of the following conditions: (1)2≤a≤3; (2)10≤b≤25; (3)c≤4; (4)15≤d≤30。 4. The solid electrolyte according to claim 1, characterized in that, The lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalateborate, and lithium hexafluorophosphate.

5. The method for preparing a solid electrolyte according to any one of claims 1-4, characterized in that, Includes the following steps: 4,4'-diaminobiphenyl-3,3'-disulfonic acid and 2,4,6-tricarboxymethylphloroglucinol were mixed in an organic solvent, sonicated, and reacted with hydrogen chloride solution. After washing and drying, TpBD-(SO3H)2 was obtained. TpBD-(SO3H)2 was then subjected to an ion exchange reaction with a lithium salt solution to obtain TpBD-(SO3Li)2. The polymer, lithium salt, and TpBD-(SO3Li)2 were dissolved in N,N-dimethylformamide solution to obtain a mixed solution; The mixed solution is dried and hot-pressed on a flat plate to obtain the solid electrolyte.

6. The preparation method according to claim 5, characterized in that, The molar ratio of the 4,4'-diaminobiphenyl-3,3'-disulfonic acid and the 2,4,6-tricarboxymethylphloroglucinol is 3:1 to 3:

3.

7. The preparation method according to claim 5, characterized in that, The organic solvent comprises dimethyl sulfoxide and N-methylpyrrolidone, and the volume ratio of dimethyl sulfoxide to N-methylpyrrolidone is 1:1; and / or, The lithium salt solution includes a lithium acetate solution.

8. The preparation method according to claim 5, characterized in that, The reaction conditions for adding hydrogen chloride solution include reacting in a constant temperature bath at 40℃~100℃ for 72~168 hours.

9. A solid-state battery, characterized in that, It includes a positive electrode, a lithium metal negative electrode, a solid electrolyte as described in any one of claims 1-4, or a solid electrolyte prepared by the preparation method as described in any one of claims 5-8.